Solve for x : 2 ( x + 1 0 ) − 5 ( 2 − x ) + 3 = 0
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The given equation is : 2 ( x + 1 0 ) − 5 ( 2 − x ) + 3 = 0 . So----->
2 ( x + 1 0 ) − 5 ( 2 − x ) + 3 = 0
⟹ 2 x + 2 0 − 1 0 + 5 x + 3 = 0
⟹ 7 x = ( − 1 3 ) ⟹ x = ( 7 − 1 3 )
right !!
2(x+10)-5(2-x)+3=0 7x+13=0 7x=-13 x=-13/7
correct
I calculated this mentally. It took me a minute.
Problem Loading...
Note Loading...
Set Loading...
2x + 20 - 10 + 5x + 3 = 0 7x + 13 = 0 7x + 13 - 13 = 0 - 13 (to isolate the 13, subtract 13 from both sides) 7x = -13 7x/7 = -13/7